The 8:55 to Baghdad - Eames, Andrew, 1958- (Woodstock, NY : Overlook Press, 2005)
The author retraces the 1928 journey by author Agatha Christie from London to Baghdad, and describes many of the places and events that influenced her novels
Includes index.
Keywords: Christie, Agatha,1890-1976 -- Knowledge -- Middle East; Christie, Agatha,1890-1976 -- Travel -- Iraq; Eames, Andrew,1958- -- Travel -- Iraq; Authors, English -- 20th century -- Biography; British -- Iraq -- History -- 20th century; Railroad travel -- Middle East; Railroad travel -- Europe; Middle East -- Description and travel; Iraq -- Description and travel; Middle East -- In literature; Iraq -- In literature